Vibralactone derivatives isolated from co-cultures of the basidiomycetes Stereum hirsutum and Boreostereum vibrans - Jinjuan Wei; Zhe-Xi Li; Gao-Ke Peng; Xinyang Li; He-Ping Chen; Ji-Kai Liu (Natural Products and Bioprospecting)
Abstract The basidiomycetes Stereum hirsutum and Boreostereum vibrans are two fungi of the same genus. In this study, chemical investigation on the co-cultures of the two congeneric fungi led to the isolation of eleven new vibralactone derivatives, hirsutavibrins A–K (1–11). The structures of 1–11 were elucidated by extensive NMR and HRESIMS spectroscopic analysis, and computational methods. Hirsutavibrins A (1) and B (2) showed weak cytotoxicity against the human lung cancer cell line A549. Hirsutavibrin D (4) showed moderate anti-nitric oxide activity in murine monocytic RAW 264.7 macrophages. This work not only expands the members of vibralactone derivatives with variable configurations but also opens a new avenue for fungal co-culturing study between congeneric fungi. Graphical Abstract